Efektivitas Penggunaan Gadget dengan Kualitas Tidur Pada Anak Sekolah Kelas IV Dan V di SD Negeri Pejuang VII Kota Bekasi - Ratih Kumala Dewi; Yuliani Agustina (Universitas Malahayati Lampung, 2024)
ABSTRACT Most internet users (by accessing gadgets) in Indonesia are people in the age group of 15-19 years. of the 171.17 million users who use the internet and it shows that it is teenagers or the younger generation who use the internet the most (APJII, 2018). The American Academy of Pediatrics, an institution that deals with the problems of school-age children in America, states that school-age children need time adequate sleep, based on research results, namely school-age children who lack sleep will experience various negative things including memory and learning disorders, physical health problems, mental health problems and are at high risk of experiencing obesity (Huda, 2016). Determine the effectiveness of the use of gadgets with sleep quality in grade IV and V children in warrior VII state elementary schools in Bekasi city. The sample of this study is partly grade IV and V school children at SD Negeri Pejuang VII in May 2023. With Random Sampling technique. The results of the Chi Square test showed that there was an effectiveness in using gadgets with sleep quality in school children in grades IV and V at SD Negeri Pejuang VII in 2023 with a total sample of 60 respondents and a P value of 0.00 (p 0.05). The effectiveness of using gadgets with sleep quality in grade IV and V school children at SD Negeri Pejuang VII in 2023. Keywords: School Age Children, Use of Gadgets, Quality of Sleep ABSTRAK Pengguna internet terbanyak (dengan mengakses gadget) di Indonesia merupakan masyarakat dalam kelompok usia 15-19 tahun. dari 171,17 juta pengguna yang menggunakan internet dan menunjukan bahwa kalangan remaja atau generasi muda yang paling banyak menggunakan internet (APJII, 2018).American Academy of Pediatris yaitu sebuah lembaga yang menangani masalah anak usia sekolah di Amerika menyatakan bahwa anak usia sekolah membutuhkan waktu tidur yang cukup, bedasarkan hasil penilitian yaitu anak usia sekolah yang kurang tidur akan mengalami berbagai hal negatif diantaranya gangguan memori dan pembelajaran, masalah kesehatan fisik, masalah pada kesehatan mental dan berisiko tinggi mengalami obisetas (Huda, 2016). Mengetahui efektifitas penggunaan gadget dengan kualitas tidur pada anak kelas IV dan V di sekolah dasar negeri pejuang VII kota Bekasi. Sampel penelitian ini sebagian anak sekolah kelas IV dan V di SD Negeri Pejuang VII pada bulan Mei 2023. Dengan jumlah sampel sebanyak 60 responden dan menggunakan teknik Random Sampling. The results of the Chi Square test show that there is effectiveness in using gadgets with sleep quality in school children in grades IV and V at SD Negeri Pejuang VII in 2023 with a P value of 0.00 (p 0.05). Adanya efektivitas penggunaan gadget dengan kualitas tidur pada anak sekolah kelas IV dan V di SD Negeri Pejuang VII tahun 2023. Kata Kunci: Anak Usia Sekolah, Penggunaan Gadget, Kualitas Tidur